مبدأ التقاضي على درجتين في الجنايات وفقا لآخر تعديل لقانون الإجراءات الجزائية 17-07 - بكوش, يوسف (roa; Vol 2 (2021): مجلة رؤى في الآداب والعلوم الإنسانية, 2021)
تعتبر محكمة الجنايات الجهة القضائية التي تفصل في أخطر القضايا، حيث أن الأحكام الصادرة عنها تمس بالحقوق الأساسية للأشخاص لذلك كان من الضروري على المشرع إعادة النظر في منظومته القانونية وذلك لتعزيز ضمانات المحاكمة العادلة للأشخاص عن طريق تطبيق مبدأ التقاضي على درجتين في هذه المحكمة.  وبالإضافة إلى أن المشرع الجزائري لم يعدل الأحكام الخاصة بمحكمة الجنايات منذ سنة 1995 بموجب الأمر 95-10، وهو ما تداركه بموجب التعديل الدستوري لسنة 2016 والذي أوجب تعديل قانون الإجراءات الجزائية بموجب القانون 17-07 واعتماد هذا المبدأ على مستوى المحاكم الجنائية، مشكلا بذلك تحولا في النظام القضائي الجزائري بعد أن كانت الأحكام الصادرة عن محكمة الجنايات لا تقبل الطعن بالاستئناف، كما أضاف أيضا تعديلات شملت هيئة الحكم بتغليب العنصر الشعبي على العنصر القضائي، وإلزامها بتسبيب الأحكام الصادرة عنها، كما أن إلغاء إجراءات التخلف عن الحضور واستبدالها بإجراءات الغياب أمام محكمة الجنايات وإعطاء المتم المتغيب الحق في الطعن بالمعارضة يعتبر أيضا من الضمانات التي جاء بها تعديل قانون الإجراءات الجزائية وتكريسا لهذا المبدأ المقرر دستوريا. الكلمات المفتاحية: محكمة جنايات ابتدائية- محكمة جنايات استئنافية- تقاضي على درجتين.   Abstract : The Criminal Court is the judicial body that adjudicates the most serious cases, as the rulings issued by it violate the basic rights of people. Therefore, it was necessary for the legislator to review its legal system in order to enhance the guarantees of a fair trial for people by applying the principle of litigation to two levels in this court.  In addition to the fact that the Algerian legislator has not amended the provisions of the Criminal Court since 1995 under Ordinance 95-10, which is what it repairs according to the 2016 constitutional amendment that necessitated amending the Criminal Procedure Law under Law17/07 The adoption of this principle at the level of criminal courts, thus constituting a shift in the Algerian judicial system after the rulings of the Criminal Court did not accept appeals to appeal, and also added amendments that included the ruling body to give priority to the popular element over the judicial component, and obligate it to cause judgments issued by it, and that The abolition of procedures for failure to attend and replace them with procedures for absence before the criminal court and giving the absentee the right to appeal the opposition is also considered one of the guarantees that came to amend the Code of Criminal Procedure and enshrining this principle established constitutionally. Keywords: A first instance criminal court - an appellate criminal court - is sued at two levels.